1990
DOI: 10.1016/0014-5793(90)80855-d
|View full text |Cite
|
Sign up to set email alerts
|

Interactions with tRNALys induce important structural changes in human immunodeficiency virus reverse transcriptase

Abstract: Retroviral RNA-dependent DNA polymerase (reverse transcriptase or RT) uses the 3'OH end of a cellular tRNA as primer to initiate DNA synthesis. Previous work with avian retrovirus has shown that reverse transcriptase is implicated in the selection of cellular virion-encapsidated tRNAs and has shown that the primer tRNA is positioned on the primer binding site near the 5' end of the viral RNA. These mechanisms support the idea that the retroviral polymerase should form complexes with primer tRNA and the specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…One obvious candidate is the reverse transcriptase (RT) polymerase, and a functional analysis of mutant HIV-1 virion particles revealed that RT is indeed involved in the selection and PBS annealing of the tRNA 3 Lys primer (45,57). Biochemical studies have provided additional information on the RT-tRNA 3 Lys complex and its involvement with the RNase H domain (17,54,56,58), but no high-resolution picture has emerged from these studies.…”
mentioning
confidence: 99%
“…One obvious candidate is the reverse transcriptase (RT) polymerase, and a functional analysis of mutant HIV-1 virion particles revealed that RT is indeed involved in the selection and PBS annealing of the tRNA 3 Lys primer (45,57). Biochemical studies have provided additional information on the RT-tRNA 3 Lys complex and its involvement with the RNase H domain (17,54,56,58), but no high-resolution picture has emerged from these studies.…”
mentioning
confidence: 99%
“…Although the mechanisms responsible for the observed reversions are unknown, the rapid reversion rates suggest that the native HIV-1 PBS is maintained because of stringent selective pressure. Both UV cross-linking and gel retardation analysis indicate that highly specific interactions between HIV-1 reverse transcriptase and its primer tRNA (6) can induce conformational changes in the heterodimeric reverse transcriptase enzyme (48,61). Studies with other retroviruses suggest that RNA sequences outside the PBS are also involved in the control of reverse transcription.…”
mentioning
confidence: 99%
“…HIV-1 RT is a very flexible enzyme [20]. Crystal structures have been determined of a complex between the heterodimeric protein and nevirapine [19,21] and other NNRTIs [22], of a ternary complex at 3 Å resolution formed by HIV-1 RT, a of 19 base/18 base double-stranded DNA (primer/template duplex) and a non-inhibitory monoclonal antibody fAb fragment [23].…”
Section: Structure Of Hiv-1 Rtmentioning
confidence: 99%